2016
DOI: 10.1371/journal.pone.0151560
|View full text |Cite
|
Sign up to set email alerts
|

Placenta-Enriched LincRNAs MIR503HG and LINC00629 Decrease Migration and Invasion Potential of JEG-3 Cell Line

Abstract: LINC00629 and MIR503HG are long intergenic non-coding RNAs (lincRNAs) mapped on chromosome X (Xq26), a region enriched for genes associated with human reproduction. Genes highly expressed in normal reproductive tissues and cancers (CT genes) are well known as potential tumor biomarkers. This study aimed to characterize the structure, expression, function and regulation mechanism of MIR503HG and LINC00629 lincRNAs. According to our data, MIR503HG expression was almost exclusive to placenta and LINC00629 was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…Originally, MIR503HG was identified to be involved in human endothelial cells and angiogenic processes . Soon afterwards, Muys et al found MIR503HG expression was increased in placenta, other reproductive tissues and 50% cancer cell lines. Then, Zhang et al found MIR503HG as an up‐regulated lncRNA in colorectal cancer tissues through analysing RNA‐seq datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, MIR503HG was identified to be involved in human endothelial cells and angiogenic processes . Soon afterwards, Muys et al found MIR503HG expression was increased in placenta, other reproductive tissues and 50% cancer cell lines. Then, Zhang et al found MIR503HG as an up‐regulated lncRNA in colorectal cancer tissues through analysing RNA‐seq datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of MIR503HG is similar to that of PLAC1 with expression found in placenta. Unlike PLAC1 , MIRG503HG expression is also found in human umbilical vein epithelial cells (HUVECS) [ 96 ]. By contrast, LINC00629 is expressed not only in the placenta but also in other tissues such as the ovary, cervix, testis and heart [ 96 ].…”
Section: Lncrnas Are Important For Trophoblast Cell Functionmentioning
confidence: 99%
“…Unlike PLAC1 , MIRG503HG expression is also found in human umbilical vein epithelial cells (HUVECS) [ 96 ]. By contrast, LINC00629 is expressed not only in the placenta but also in other tissues such as the ovary, cervix, testis and heart [ 96 ]. MIR503HG is localised to the nucleus of JEG-3 cells, while LINC00629 is found evenly throughout the cell.…”
Section: Lncrnas Are Important For Trophoblast Cell Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…11995065). The other cells lines used in the tumor cell line panel to compare with normal tissues were previously described 36 . All mediums were supplemented with 10% FBS (GE Healthcare, Catalog No.…”
Section: Cell Culture Maintenancementioning
confidence: 99%